Evaluation of Fibronectin Expression in Peripheral and Central Giant Cell Granulomas of the Jaws and Giant Cell Tumor of the Bone Using Immunohistochemistry - Nasrollah Saghravanian; Narges Ghazi; Amir Hossein Jafarian; Abdullah Javan Rashid; Amin Mirjordavey (Mashhad University of Medical Sciences, 2021)
Introduction: This study aimed to evaluate the Fibronectin expression in peripheral and central giant cell granulomas (PGCG and CGCG) of jaws and giant cell tumor (GCT) of bone using immunohistochemistry. Materials and Methods: In this retrospective study, PGCG (n=15), CGCG (n=15), and GCT (n=10) samples were selected from the archives of Dental School and Ghaem Hospital, Mashhad, Iran. Distribution pattern, staining pattern, and intensity of Fibronectin expression in extracellular matrix were investigated using the immunohistochemistry method according to the manufacturer's instructions. Results: Regarding the intensity of expression, 26 (65%) samples showed strong expression. On the other hand, 64.3 % of the PGCG samples demonstrated weak expression, whereas 46.3% of the CGCG samples showed strong immunoreactivity. There was a statistically significant difference between PGCG and GCT in terms of strong and weak expression. Furthermore, the Reticulate-Fibrillar staining pattern was observed in 19 samples. The Reticulate-Fibrillar and Fibrillar in CGCG lesions and Reticular patternin PGCG lesions were the most prevalent patterns. A statistically significant correlation was reported between the staining pattern and the type of the lesion. The uniform distribution pattern was observed in 33 samples; in addition, it showed the most distribution in CGCG, and most cases of the focal distribution pattern were observed in the PGCG lesions. The distribution pattern was not related to the type of lesion. Conclusions: The findings of the present study showed more similarity between CGCG and GCT lesions regarding Fibronectin immunoreactivity. Therefore, further studies are required to evaluate the similar pathogenesis of these lesions.